An assessment of the effectiveness of the Crossways Farm Village constructed wetland in the treatment of domestic wastewater - Silbernagl, Ryan (Rhodes University, Faculty of Science, Department of Geography, 2020)
A mass balance study was conducted comparing inflowing and outflowing solute loads in order to calculate the treatment efficiency of a free water surface (FWS) constructed wetland used to treat domestic wastewater following primary treatment in an anaerobic reactor and oxidation in a rotating biological contractor. Water samples were taken at six locations down the length of the treatment system and analysed for nitrate nitrogen (NO3-N), nitrite nitrogen (NO2-N), ammonia nitrogen (NH4-N) and phosphorus as phosphate (PO4-P). Flow was determined using two V notch weirs combined with pressure transducers based on an empirically derived stage-discharge relationship. The concentration of each solute (g.m-3) multiplied by flow (m3.day-1) provides a measurement of the mass of each solute entering and leaving the treatment wetland such that the difference (inflow "“ outflow) indicates the nett storage in, or loss from, the wetland. In order to determine the water balance, apart from measuring surface inflows and outflows, rainfall was measured using an onsite rain gauge. Evapotranspirational losses were determined using the Penman-Monteith equation based on weather data collected at an onsite weather station. Other than water that entered the wetland via the primary water treatment works, surface inflows could be ignored as the wetland was sealed with a plastic liner, which also prevented groundwater inflow and outflow. Wetland outputs via surface outflow and evapotranspiration were then subtracted from wetland inputs to determine the water balance over the study period. Approximately 10.5% of water inputs into the hydrological mass balance calculation was not accounted for, which is considered to be accounted for by inaccuracy associated with the estimation of evapotranspiration and possibly by differences in water levels in the wetland at the start and end of the experiment. Total input, output and storage of NO3-N, NO2-N, NH4-N and PO4-P was calculated from April 2016 to September 2016 to give the treatment efficiency of the FWS wetland system. Results showed a 91.5% reduction in NO3-N, 76.6% reduction in NH4-N, and 88.8% reduction in PO4P between the inflow and outflow. Wetland sediment and vegetation (Typha capensis) samples were also analysed for nitrogen and phosphorus content to give an estimate of nutrient stocks/storage accumulated in plant tissues and sediments over the lifespan of the wetland. Standing stock calculations showed that a total of 450.1kg of nitrogen is stored in the wetlands, of which 69.3kg is stored in wetland sediments. Wetland phosphorus retention was found to be significantly lower with a total of 57.1kg of phosphorus, of which 77.4% was stored in sediments, indicating that wetland sediments comprise the largest store and therefore removal pathway of nutrients in the Crossways Farm Village FWS wetland.
Keywords: Crossways Farm Village FWS wetland (South Africa)-- Management; Sewage -- Purification -- South Africa; Wetland management -- South Africa